The analyzing finishing quality based on several of shape / Azlina A. Aziz - A. Aziz, Azlina (2004)
Wood finishing is the last process for product surfaces when we can add with some layers for purpose of protection and visual appearance. This status to get the high quality level in wood finishing, we must have correct equipment and associated accessories. Using the spray gun for finishing very popular in furniture industry. Although it is added cost for maintenance, the spray gun is the best equipment because to get the good job with effective and efficiently. Beside that, the correct technique are important such as the distance of spray from work pieces surface, the angle of spray product, moving the spray gun and types of work piece (panel or three dimension).